(3YbO GdUdM ai GdbGfhf GdhVYi hGdTQjYI GdGSdGejI (B: s (3OQGSI ebGQfI (B/ s - (3QeVGf NVQ SGde TeS GdOjfs; (3Ydi MSjf fLjOgs; (3eMeO fLjH YhVjf s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2008)
(3JfGhd gPG GdHMK GdehVhYGJ GdeJYdbI HYbO GdUdM ShGA ai GdbGfhf GdhVYi Ch ai GdTQjYI GdGSdGejI eY GdebGQfI HjfgeG bOQ eGCecf JWHjbG defgL GdOQGSI GdebGQfI GdPi GdJRe Hg GdHGMK ai NWI GdHMK hbO bSe gPG GdHMK Gdi aUd JegjOi hKdGKI CHhGH QFjSjI hNUU GdHGMK GdaUd GdJegjOi dHjGf CgejI YbO GdUdM heLGdGJgs
(3GWQhMI(B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdeOfi, (B2008s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B: (3UaMI (B373-390s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdeOfjs; (3GdTQjYI GdESdGejIs; (3GdbGfhf GdhVYis; (3YbO GdUdMs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs